Interface Direct Shearing Behavior Between Soil and Saw-tooth Surfaces by DEM Simulation. (2017) - Jing, Xue-Ying; Zhou, Wan-Huan; Li, Yangmin
Abstract: The shearing behavior of a soil-structure interface is influenced by the properties of both the soil and the structure (e.g., particle shape, structural hardness, and surface roughness). While previous investigations using experimental approaches have been able to characterize the macroscopic behavior of the soil–structure interface, the micro-mechanisms behind these observations made from a laboratory still require explanation. This study aims to analyze the effect of roughness on the shearing behavior of the soil-hard structure interface. To do so, we performed a series of three-dimensional interface shear tests using the discrete element method with various degrees of normalized roughness. A standard saw-tooth was chosen to represent the geometry of an artificial rough surface. The results show that: (1) shear stress softening is observed after peak when the specimen shearing is on a rough interface, (2) the shear strength of a soil-structure interface increases as the interface roughness increases, and (3) dilatancy occurs when the roughness is sufficiently large. The incremental shear displacement field indicates that during the shearing process the shear deformation is largely localized in a narrow zone adjacent to the interface, called the shear band. A discontinuous feature is characterized after the shear band appears. The thickness of the shear band varies depending on the roughness of the interface. Specimen shearing on a rougher interface tends to create a thicker shear band.